2008
DOI: 10.1158/1078-0432.ccr-07-1873
|View full text |Cite
|
Sign up to set email alerts
|

Transformation by Oncogenic Mutants and Ligand-Dependent Activation of FLT3 Wild-type Requires the Tyrosine Residues 589 and 591

Abstract: Purpose: Mutations in the receptor tyrosine kinase FLT3 are found in up to 30% of acute myelogenous leukemia patients and are associated with an inferior prognosis. In this study, we characterized critical tyrosine residues responsible for the transforming potential of active FLT3-receptor mutants and ligand-dependent activation of FLT3-WT. Experimental Design: We performed a detailed structure-function analysis of putative autophosphorylation tyrosine residues in the FLT3-D835Y tyrosine kinase domain (TKD) mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…This results in only a fraction of phosphorylated JM Flt3 AL mutant relative to Flt3 ITD to undergo the same processing delay as Flt3 ITD. This is supported by the report of Tyr589/591 also being required for ligand-independent proliferation of cells expressing Flt3 AL (Vempati et al, 2008). The non-phosphorylated JM Flt3 AL fraction is efficiently processed and traffics to the plasma membrane, and would transmit downstream signals similarly to those of Flt3 WT.…”
Section: A Working Model Of Differential Signalingsupporting
confidence: 52%
“…This results in only a fraction of phosphorylated JM Flt3 AL mutant relative to Flt3 ITD to undergo the same processing delay as Flt3 ITD. This is supported by the report of Tyr589/591 also being required for ligand-independent proliferation of cells expressing Flt3 AL (Vempati et al, 2008). The non-phosphorylated JM Flt3 AL fraction is efficiently processed and traffics to the plasma membrane, and would transmit downstream signals similarly to those of Flt3 WT.…”
Section: A Working Model Of Differential Signalingsupporting
confidence: 52%
“…Y589 and Y591 have been identified as Src association sites [26] and involved in the activation of STAT5 [34]. Moreover, these two residues were shown to be crucial for the transforming potential of FLT3-ITD and D835Y as well as for the ligand-dependent activation of wild-type FLT3 [42]. Y599 was demonstrated to be involved in binding of the protein tyrosine phosphatase SHP2 [26].…”
Section: Discussionmentioning
confidence: 99%
“…This result agrees with the assumption that SRC binding to FLT3-ITD is essential for robust STAT5 activation and with the results of previous studies demonstrating that tyrosine residues 589/591 in FLT3-ITD are essential for strong STAT5 activation and for the induction of myeloproliferative disease in mice. 28,35,36 SRC SH2-mediated binding to tyrosine 589/591 requires phosphorylation of these sites. To compare the level of phosphorylation at tyrosine 589/591 in FLT3-ITD, FLT3-TKD, and FLT3-WT after ligand stimulation, we used site-specific anti-pY Abs ( Figure 2C).…”
mentioning
confidence: 99%
“…36 Vempati et al showed that the tyrosines 589 and 591 are also important for growth of Ba/F3 cells expressing FLT3-WT stimulated with FL or FLT3-TKD. 28 Previous studies have compared the signaling of FLT3-ITD and FLT3-TKD and demonstrated that the localization of FLT3-ITD and FLT3-TKD significantly alters the transforming capability and activation of downstream signaling molecules. In the case of FLT3-ITD, retention in the endoplasmic reticulum was suggested One representative of at least 3 independent experiments is shown.…”
mentioning
confidence: 99%
See 1 more Smart Citation